(untitled) (CIPEEX, 2022)
AUTISTIC SPECTRUM DISORDER (ASD) IS A GROUP OF HETEROGENEOUS NEUROPSYCHIC DISORDERS THAT AFFECTS LANGUAGE, COGNITION AND SOCIAL INTERACTION. THE OBJECTIVE OF THIS STUDY WAS TO DESCRIBE THE BIOLOGICAL AND ENVIRONMENTAL INFLUENCES IN THE DEVELOPMENT OF AUTISM SPECTRUM DISORDER AND ITS PSYCHOSOCIAL REPERCUSSIONS. THE ETIOLOGY OF ASD IS MULTIFACTORIAL. IT WAS OBSERVED THAT 2% OF THE CAUSES ARE ASSOCIATED TO CHROMOSOMAL ABNORMALITIES, 10% TO MICRO-DUPLICATIONS AND MICRO-DELETIONS, 5% TO MONOGENIC DISEASES, 3% TO ENVIRONMENTAL CAUSES, AND 80% TO MULTIFACTOR AND EPIGENETIC CAUSES. THE MATERNAL CAUSES - FOCUS OF THIS STUDY - ARE RELATED TO A HIGHER INCIDENCE OF ASD. HIGH MATERNAL CRP IS ASSOCIATED WITH THE RISK OF AUTISM. POSITIVITY TO ANTI - TPO ANTIBODIES DURING PREGNANCY INCREASED THE CHANCE OF DEVELOPING AUTISM IN CHILDREN BY 80%. CHILDREN EXPOSED TO PREGNANCY-SPECIFIC HYPERTENSIVE DISEASE WERE TWICE AS LIKELY TO BE DIAGNOSED WITH ASD. THE MODE OF DELIVERY MOST ASSOCIATED WITH ASD WAS ELECTIVE CESAREAN DELIVERY. REGARDING THE PSYCHOSOCIAL REPERCUSSIONS, IT IS NOTICED THAT THE TIME DEDICATED TO THESE CHILDREN IS HIGH AND IT HARMS THE HEALTH AND THE PERSONAL LIFE OF THE CAREGIVERS. THE LACK OF PREPARATION OF THESE IS AN AGGRAVATING FACTOR OF THE DIFFICULTY OF COMMUNICATION AND INCLUSION OF THE AUTISTIC. THE LONGER THE PROFESSIONAL FOLLOW-UP, THE GREATER THE SOCIAL INTERACTION. THEREFORE, IT IS CONCLUDED THAT, AMONG THE BIOLOGICAL INFLUENCES ON ASD IN CHILDREN, THE GENETIC IMPLICATIONS ARE THE MOST RELEVANT, HOWEVER, THE ENVIRONMENTAL ONES ARE AS PRESENT AS, ESPECIALLY MATERNAL CAUSES. THE SOCIAL REPERCUSSIONS OF ASD SEVERELY AFFECT THEIR INTERPERSONAL RELATIONSHIPS.